Existency of Green Coconut Fruit (Cocos nucifera Linn Var. Viridis) as a Sufi Education Media - Hartono, Djoko; A'yun, Qurrotul; Aliyah, Himatul (Journal Intellectual Sufism Research (JISR), 2021)
Every word that is mentioned by Allah in the Qur'an, is related to giving lessons to humans or inviting people to think. In Al-Qur’an, Surah An-Nur:35, explained that the nature of Allah's light in the form of a parable, something that was known to the people at that time, namely the olive tree. Indonesian scholars interpret it as a coconut tree. This research uses literature study method with phenomenological analysis, functionalism analysis and critical analysis . The results are Coconut has an important meaning in Indonesian public belief. People believe that the coconut fruit is a symbol that represents the spiritual life of humans towards the divine. The use of the coconut fruit symbol has been used by Sufi scholars in delivering advice which is full of philosophical meanings. Each part of the coconut fruit has its own meaning representing a spiritual journey to the Divine. Coconut skin and coir as Sharia. The use of green coconut fruit as a medium for Sufi education is expected to provide Sufis with good and easy to understand learning so that Sufis can take the knowledge given by their teachers.